Membangun budaya literasi informasi bagi masyarakat kampus - Riska Darmayanti (UIN Sumatera Utara, 2016)
This article discuss how information literacy is built at university.Information literacy is a person's ability to search , collect , evaluate or interpret , use and communicate information from a variety of sources effectively.